Classroom Learning with Active Learning Approach: A Systematic Literature Review - Sari, Shindia Fatika; Roulina, Fenny; Nurlaila, Nurlaila; Eliza, Eliza; Siswanti, Siswanti (PPSDP International Journal of Education, 2025)
This systematic literature review explores active learning approaches in educational settings, particularly classroom learning. This study used the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) to conduct a systematic study of classroom learning with active learning approaches. A systematic literature search was conducted to identify and retrieve empirical studies between 2022 and 2024. Key findings revealed the significant impact of active learning approaches on classroom learning. These methods, which include Active Learning Pedagogy Sequence (ALPS) learning, ARCS (Attention, Relevance, Confidence, Satisfaction) Model, Problem-based Projects and Cooperative Learning, Flipped Classroom Approach, Use of ChatGPT, Utilization of Mobile Technology, and more, have consistently demonstrated their effectiveness in increasing learner engagement, motivation, satisfaction, knowledge acquisition, skill development, and knowledge retention. For example, a study by Jiang (2024) showed that the integration of technology such as ChatGPT can encourage students’ self-directed exploration, resulting in higher achievement compared to traditional passive learning. Dorée and Quinn (2024) proposed ALPS to enhance student engagement and support instructors’ development of teaching skills. Ko (2024) described the use of storytelling and story-making to enhance class engagement, while (Yuni et al., 2024) emphasized the effectiveness of simulations, role-playing, and problem-based projects in enhancing student collaboration and motivation.